Implementasi Pengamanan Pesan Chatting menggunakan Metode Vigenere Cipher dan Cipher Block Chainning - Sahara, Helmi (MEANS (Media Informasi Analisa dan Sistem), 2018)
Along with the increasingly rapid development of technology at this time, causing security is a very important thing. In this era, there are many terms of chatting. Chatting is a form of communication that is usually carried out between two people or more directly or realtime by utilizing network facilities. Various ways can be done by irresponsible parties to damage, hack our chat facilities, and therefore need security. To overcome this so that chat messages are safe from unauthorized users, we need a software that can do a message encryption / decryption process. In this paper we discuss the implementation of the Vigenere Cipher method and Chainning Cipher Block for the encryption / decryption process of securing chat messages.